Alkannin-Induced Oxidative DNA Damage Synergizes With PARP Inhibition to Cause Cancer-Specific Cytotoxicity - Chang, Mingxin; Wang, Hongge; Niu, Jiajing; Song, Yan; Zou, Zhihua (Frontiers in Pharmacology, 2020)
Oncogenic transformation is associated with elevated oxidative stress that promotes tumor progression but also renders cancer cells vulnerable to further oxidative insult. Agents that stimulate ROS generation or suppress antioxidant systems can drive oxidative pressure to toxic levels selectively in tumor cells, resulting in oxidative DNA damage to endanger cancer cell survival. However, DNA damage response signaling protects cancer cells by activating DNA repair and genome maintenance mechanisms. Thus, combining pro-oxidative agents with inhibition of DNA repair may produce synergistic cancer-specific cytotoxicity. The natural naphthoquinone alkannin has been shown to elevate cellular ROS levels through redox cycling. Here we show that sublethal doses of alkannin induced ROS elevation and oxidative DNA damage in colorectal cancer but not normal colon epithelial cells. Blocking DNA repair with the PARP inhibitor olaparib markedly synergized with alkannin to yield synthetic lethality in colorectal cancer cells at nontoxic doses of both drugs. Synergy between alkannin and olaparib resulted from interrupted repair of alkannin-induced oxidative DNA damage and PARP-trapping, as it was significantly attenuated by NAC or by OGG1 inhibition and the non-trapping PARP inhibitor veliparib did not yield synergism. Consequently, coadministration of alkannin and olaparib caused intense replication stress and DNA strand breaks, leading to apoptosis after G2 arrest in colorectal cancer cells and significant suppression of tumor xenografts in vivo. Hence, the combination of alkannin with olaparib provides a promising therapeutic strategy that exploits a cancer vulnerability common to most tumor cells.